The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1097/dcr.0000000000000608
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Indocyanine Green Fluorescence Imaging–Guided Complete Mesocolic Excision in Laparoscopic Flexural Colon Cancer Surgery

Abstract: Intraoperative real-time visualization of the lymph flow using indocyanine green fluorescence imaging during laparoscopic colon cancer surgery, especially flexural colon cancer surgery, is feasible and a helpful technique for identifying appropriate central vessels to be dissected and for determining an appropriate separation line of the mesentery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 26 publications
2
49
0
Order By: Relevance
“…In the present study, we had visualisation of the lymphatic drainage in all patients. Earlier studies also described the safety, feasibility, and high success rate of ICG FI in this application [30,33,34]. In our sample, the lymphatic drainage was partially demonstrated in 3 patients, insufficient to guide the lymphadenectomy.…”
Section: Ten Consecutive Patients With a Diagnosis Of Colon Cancer Unsupporting
confidence: 48%
See 1 more Smart Citation
“…In the present study, we had visualisation of the lymphatic drainage in all patients. Earlier studies also described the safety, feasibility, and high success rate of ICG FI in this application [30,33,34]. In our sample, the lymphatic drainage was partially demonstrated in 3 patients, insufficient to guide the lymphadenectomy.…”
Section: Ten Consecutive Patients With a Diagnosis Of Colon Cancer Unsupporting
confidence: 48%
“…Prior work has supported the value of ICG FI to identify aberrant nodes [28,30,[35][36][37]. [22,26,29,30,33,34,[38][39][40][41]. We have previously reported our technique of subserosal injection to visualize lymphatic drainage in a colon cancer patient [12].…”
Section: Ten Consecutive Patients With a Diagnosis Of Colon Cancer Unmentioning
confidence: 93%
“…More novel uses of ICG have been recently described including identification of sentinel nodes and lymphatics (10). Prior studies have shown the efficacy and ability to visualize the mesenteric and central vessels for ligation (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence imaging using appropriate fluorophores may help achieve this. Prior studies have shown the efficacy and ability to visualize mesenteric bound and central vessels for ligation . The technology can be applied to more precise surgery, especially in right colon cancers, with the tool guiding an optimal oncological resection and avoiding the need for a CME, with its associated risks.…”
mentioning
confidence: 99%
“…Prior studies have shown the efficacy and ability to visualize mesenteric bound and central vessels for ligation. 11,12 The technology can be applied to more precise surgery, especially in right colon cancers, with the tool guiding an optimal oncological resection and avoiding the need for a CME, with its associated risks.This concept was successfully tested in a 73-year-old female presenting with a colon adenocarcinoma who underwent a laparoscopic right hemicolectomy. Once the colon was fully mobilized and the Ileocolic vessel ligated, the specimen is externalized.…”
mentioning
confidence: 99%